2004
DOI: 10.1152/jn.00347.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subthreshold Up and Down States on the Whisker-Evoked Response in Somatosensory Cortex

Abstract: Changes in spontaneous activity within the cortex recognized by subthreshold fluctuations of the membrane potential of cortical neurons modified the response of cortical neurons to sensory stimuli. Sensory stimuli occurring in the hyperpolarized "down" state evoked a larger depolarization and were more effective in evoking action potentials than stimuli occurring in the depolarized "up" state. Direct electrical stimulation of the thalamus showed the same dependence on the cell's state at the time of the stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
158
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(200 citation statements)
references
References 77 publications
38
158
4
Order By: Relevance
“…However, our results show that the increased cortical responses are directly related to the slower/more silent cortical spontaneous activity, thus offering an additional mechanism to explain immediate changes in cortical responses after deafferentation. In the rat somatosensory system, brief peripheral stimuli evoke larger cortical responses when the cortex is in a silent compared to an active state (Petersen et al, 2003;Sachdev et al, 2004), particularly when the stimuli themselves are able to trigger active states associated with the responses (Hasenstaub et al, 2007;Reig and Sanchez-Vives, 2007). This inverse relation between the level of spontaneous activity and the amplitude of evoked responses is clearly present in our data.…”
Section: Relation Between Cortical Spontaneous Activity and Evoked Resupporting
confidence: 60%
“…However, our results show that the increased cortical responses are directly related to the slower/more silent cortical spontaneous activity, thus offering an additional mechanism to explain immediate changes in cortical responses after deafferentation. In the rat somatosensory system, brief peripheral stimuli evoke larger cortical responses when the cortex is in a silent compared to an active state (Petersen et al, 2003;Sachdev et al, 2004), particularly when the stimuli themselves are able to trigger active states associated with the responses (Hasenstaub et al, 2007;Reig and Sanchez-Vives, 2007). This inverse relation between the level of spontaneous activity and the amplitude of evoked responses is clearly present in our data.…”
Section: Relation Between Cortical Spontaneous Activity and Evoked Resupporting
confidence: 60%
“…Slow oscillations of neuronal membrane potential between the up and down states at frequencies Ͻ1 Hz have been observed in various regions of the brain during slow wave sleep (Steriade et al, 1993a;Timofeev et al, 2001) or under anesthesia (Steriade et al, 1993b,c;Wilson and Kawaguchi, 1996;Anderson et al, 2000;Petersen et al, 2003;Sachdev et al, 2004). Even in awake animals, similar membrane potential fluctuations have been observed (Timofeev et al, 2001;Kitano et al, 2002;Petersen et al, 2003), but the durations of the up and down states tend to be shorter, typically on the order of tens of milliseconds (Steriade et al, 1993a;Timofeev et al, 2001;Destexhe and Sejnowski, 2003).…”
Section: Introductionmentioning
confidence: 87%
“…Slow oscillations in many brain regions interact strongly with sensory-evoked responses (Arieli et al, 1996;Petersen et al, 2003;Sachdev et al, 2004). For example, recordings from anesthetized or awake rats showed that whisker stimulation evoked larger depolarizing postsynaptic potentials and more spikes in cortical cells in the down state than in the up state (Petersen et al, 2003;Sachdev et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Up and down states have been described and characterized for several decades (Cowan and Wilson, 1994;Steriade et al, 1993a,b;Wilson and Groves, 1981). More recently, the bistability of the membrane potential has been described in-vitro (Cossart et al, 2003;Sanchez-Vives and McCormick, 2000), as well as in-vivo in frontal cortical areas (Lewis and O'Donnell, 2000;Léger et al, 2005), somatosensory (Petersen et al, 2003a;Sachdev et al, 2004;Steriade et al, 2001;Timofeev et al, 2001), visual (Anderson et al, 2000;Lampl et al, 1999), olfactory (Luo and Katz, 2001;Margrie and Schaefer, 2003), other areas (Paré et al, 1998), and striatum (Kasanetz et al, 2002;Mahon et al, 2003;Stern et al, 1997;Wilson and Kawaguchi, 1996).…”
Section: Up and Down States In The Cerebral Cortexmentioning
confidence: 99%
“…Large, persistent changes in membrane potential can also occur in a response to behavioral state changes , or sensory stimulation (Anderson et al, 2000;Carandini and Ferster, 1997). Up and down states have been observed in frontal cortical areas (Lewis and O'Donnell, 2000;Léger et al, 2005), somatosensory (Sachdev et al, 2004;Steriade et al, 2001), visual (Lampl et al, 1999), olfactory areas (Luo and Katz, 2001;Margrie and Schaefer, 2003), striatum (Stern et al, 1997;Wilson and Kawaguchi, 1996), and many others.…”
mentioning
confidence: 99%